O discurso educativo da atuação profissional do agente de combate às endemias (ACE) em políticas públicas do Sistema Único de Saúde (SUS) - Silva, Andréa Cardoso da (2024)
The present work, produced in the Cultural Studies in Education Research Line, is located in the education and health thematic axis. In the light of Michel Foucault's Archaeological Discourse Analysis - AAD, outlined in his book The Archeology of Knowledge (2008), this Dissertation records the set of findings resulting from the master's research that had as its research object the educational discourse of professional performance of the Agent to Combat Endemic Diseases (ACE) in the Public Policies of the Unified Health System (SUS). ACE is a health worker whose role is focused on disease surveillance and control, care and health promotion for the Brazilian population, whose role was linked to the SUS on October 5, 2006, in Law No. 11,350 and its work activities specified on January 5, 2018, in Law No. 13,595. However, despite the recognition of their function and activities, only on January 20, 2023, their work was regulated as a health profession, through Law No. 14,536. In view of the above and considering the spectrum of activities in the ACE work field, this research focused on the development of its educational actions, delimiting the research at the level of analysis of the educational discourse of SUS public health policies. Institutional discourse that governs ACE’s educational saying and doing. The problem question was: what educational discursive order constitutes the professional performance of the Agent to Combat Endemic Diseases (ACE) in Public Policies of the Unified Health System? Based on the AAD and the contributions of Alcantara and Carlos (2013), the research adopted the following procedures: mapping, analysis and description of the sources and the discourse-object of the research. Three source documents and some related documents, which standardize the national health education policies of the SUS, were analyzed and described, which made it possible to identify three bundles of enunciative relationships, constitutive of the order of discourse, in which the tasks are located and carried out. ACE educational actions, namely: health education, continuing health education and popular health education. It is expected that the research will contribute to elucidating the educational discourse of ACE within the SUS, while demonstrating the investigative potential of AAD, as a possibility of carrying out qualitative research in education, health education and in the field of cultural studies in education .